1998
DOI: 10.1080/00049189808703207
|View full text |Cite
|
Sign up to set email alerts
|

Measuring short‐term population mobility among indigenous Australians: options and implications

Abstract: "Despite the fact that indigenous Australians are known to be frequently mobile over the short term, statistical information regarding this population movement is grossly deficient.... This paper examines various means by which short-term population movement can be quantified to yield aggregate indicators of demographic impact. First, census data are used to establish the rate and pattern of inter-regional, short-term displacement. This reveals regional urban centres as net recipients of temporary residents wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 8 publications
0
34
0
Order By: Relevance
“…Ethnographically, population distribution has been linked to resource availability and extensive studies exist about resource availability, mobility, and population densities (Keeley 1988, Taylor 1998). For example, among Pumé mobile hunter-gatherers living on the Llanos of Venezuela, camp membership includes bilateral kin and remains stable across all seasonal moves.…”
Section: Parameter 3: Social Resourcesmentioning
confidence: 99%
“…Ethnographically, population distribution has been linked to resource availability and extensive studies exist about resource availability, mobility, and population densities (Keeley 1988, Taylor 1998). For example, among Pumé mobile hunter-gatherers living on the Llanos of Venezuela, camp membership includes bilateral kin and remains stable across all seasonal moves.…”
Section: Parameter 3: Social Resourcesmentioning
confidence: 99%
“…Housing is of particular significance, as housing distress may drive higher rates of mobility (Belanger, Awosoga, and Weasal Head 2013), and yet the federal government has for decades neglected the housing needs of the Aboriginal population seeking to establish itself in the city, and has focused rather on reserve-based housing (Belanger, Weasal Head, and Awosoga 2012). Internationally, it has been argued that urban service providers have difficulties meeting the transitional needs of mobile Indigenous populations, largely due to complications in providing continuous and adequate care to non-stationary populations (Clatworthy and Norris 2007;CMHC 2002;Prout and Yap 2010;Taylor 1998). According to the United Nations (2010), Indigenous peoples' urban mobility remains an ongoing priority area, as frequent Indigenous movers often experience limited access to health, housing, employment, and education services, broadly due to a lack of adequate access to information, and to resistance on the part of dominant governance structures to acknowledging and valuing Indigenous peoples' right to self-determination and ways of knowing, including participation in, and co-creation of, urban planning and the management of services.…”
mentioning
confidence: 99%
“…Aboriginal mobility is often construed as a negative practice (Cooke and McWhirter 2011), and it has been suggested that frequent movement may disrupt or have a negative impact on service delivery (Clatworthy and Norris 2007;Prout 2009;Taylor 1998). While research has examined how service provision and government funding affect the identity of First Nations women living in urban areas (Peters 2006), and has documented Indigenous mobility patterns and flows over the past half-century (Norris and Clatworthy 2011), little to no work has examined the relationship between service delivery and mobility.…”
mentioning
confidence: 99%
“…One complicating issue for the Indigenous population is the prevalence of short-term circular movement in the overall context of total mobility (Taylor 1998;Taylor & Bell 2004), although in many remote regions, such as the Pilbara, the same can be said for the non-Indigenous population as well (Bell 2001;Bell & Ward 2000).…”
Section: Indigenous Population Projection Assumptionsmentioning
confidence: 99%